Factors influencing intention to adopt a minimalist lifestyle among young consumers in Bahau, Negeri Sembilan, Malaysia - Hashim, Ahmad Hariza; Loi, Sin Nee; Mohd Khairan, Nur Aishah (Human Resource Management Academic Research Society, 2023)
The practice of minimalism has the potential to enhance living standards, and work output, change consumer consumption behaviour, and ultimately lessen the problem of domestic waste to the environment and create a better world for all people. Minimalism encourages consumption reduction, which lessens its negative effects on the environment. Today's youth perceive themselves as being more environmentally friendly in their daily actions. Therefore, the goal of this study is to identify the variables that can affect young consumers' intentions to adopt a minimalist lifestyle. One hundred and twenty young consumers living in Bahau, Negeri Sembilan, Malaysia were chosen using the mall intercept approach. They were questioned about their environmental concern, intentions to live minimally, attitudes, subjective norms, and perceived behaviour control concerning minimalism. The respondents indicate a strong desire to live a minimalist lifestyle in the future, but a moderate level of environmental concern. Only perceived behaviour was determined by the study to be a reliable predictor of the intention to live a minimalist lifestyle. Interestingly the study shows that environmental concern did not show a significant relationship with minimalist lifestyles. Therefore, more need to be done on creating environmental awareness among younger consumer and relating it to a minimalist lifestyle.